Proposal to purchase new projectors: for teaching and learning classes and labs Kulliyyah Architecture & Environmental Design International Islamic University Malaysia - Mustafa, mohd mizam; Ayob, Mohd Fairullazi (2018)
To seek approval for the purchase of new 10 fixed projectors at Kulliyyah of Architecture & Environmental Design in International Islamic University Malaysia.